Polymers additive for improving the flow properties of lubricating oil - S.I. Shara; E.A. Eissa; J.S. Basta (Egyptian Journal of Petroleum)
An investigation was conducted for the improvement of the physical properties of Lubricating oil. The copolymer used is ethylene propylene diene monomer (EPDM). The oil viscosity index (VI) and viscosity/temperature characteristics were improved at different concentrations 2468 and 10% by weight solutions. The efficiency of the additive as viscosity index and flow improvers was investigated. FT-IR analysis determines the change in the carbonyl group. Thermo gravimetric analysis (TGA), is used to study the degradation and thermal stability of the studied base stock samples. Keywords: Lubricating oil, Copolymer (EPDM) viscosity index, FT-IR spectroscopy, Thermogravimetric analysis